Osteomyelitis of Jaw: A Case Report - Dolly Prashant; Viplav Prashant (International Journal of Medical Research and Review, 2022)
Tubercular (TB) osteomyelitis of mandible is a rare and uncommon clinical condition. The clinical appearance of tubercular infection of temporomandibular joint (TMJ) comprises of nonspecific features resembling osteomyelitis, arthritis, or any other kind of chronic joint diseases. At times, localized painful swelling of the jaw may be the only manifestation. The presented case is of osteomyelitis of the jaw in a 14-year-old girl patient for whom TB was later suspected.